Twentieth-century Victorian : Arthur Conan Doyle and the Strand magazine, 1891-1930 - Cranfield, Jonathan (Edinburgh critical studies in Victorian culture., 2016)
A literary history of Arthur Conan Doyle's work with the Strand Magazine in the twentieth century. You know Arthur Conan Doyle as the stereotypically 'Victorian' author of the Sherlock Holmes stories which, on the lavishly-illustrated pages of the Strand Magazine, captivated and defined the late nineteenth-century marketplace for popular fiction and magazine publishing. This book tells the story of that relationship and the aftermath its enormous success as author and publication sought to shepherd their determinedly Victorian audience through the problems and crises of the early twentieth century. Here you can discover the Conan Doyle who used his public platform to fight for divorce reform, for the rights of colonised peoples, for State welfare programmes, for the abolition of blood sports and who, even in his last years, foresaw the coming of the Second World War, the Cold War and the age of weapons of mass destruction. The twentieth-century Conan Doyle was not a man with his eyes fixed upon the past but determinedly responding to a changing world with as much vigour and commitment as any modernist writer. Key Features. Original approach to Conan Doyle as a 'popular modernist' Analyses many forgotten and neglected novels, short stories, letters, pamphlets and non-fiction pieces, many of which have gone entirely unremarked within existing criticism Provides new periodical context by using forgotten material from the Strand to situate the work of Conan Doyle (and other popular writers from the period) within their historical moment Draws on original research into the artistic and business history of the Strand magazine, its writers and its employees